ENCOURAGING STUDENTS' ENVIRONMENTAL AWARENESS THROUGH ECO-ELT-BASED TEXTBOOKS - Nadiyah, Faridatun; Lestari, Iin Widya; Putri, Nanin Verina Widya; Tauchid, Ahmad (Universitas Muhammadiyah Makassar, 2024)
This development research aims to develop Eco-ELT textbooks for young learners. This research uses the Research and Development (RD) method with the 4-D (Four D) model. The development steps carried out by researchers are 1). Define, 2). Design, 3). Develop, and 4). Disseminate. The participants in this research were 31 fourth-grade elementary school students, 14 students from SDN Glagahwangi 1, and 17 students from SDN Glagahwangi 2. Data collection techniques used interviews and Likert scale questionnaires to obtain responses. Validation is carried out by material expert and media expert. To determine the suitability of the product is obtained from the results of trials and responses from educators and students. The media developed was tested on 14 fourth-grade students at SDN Galagahwangi 1 Sugihwaras Bojonegoro. The results of material expert validation produced a score of 122 with a percentage of 97.6%, including very valid criteria related to contextual evaluation factors, practicality, and suitability of content. With very valid criteria, the average score for graphic feasibility elements obtained in media expert validation was 95% with a total score of 129. In limited-scale testing, students at SDN Glagahwangi 1 Sugihwaras Bojonegoro obtained an average score of 92.5% of the total score of 972 is a very worthy criterion. Meanwhile, the average answer score from educators is 94% with a total score of 141 which is in the very worthy range. From these results, it is concluded that Eco-ELT-based textbooks for young students are adequate and appropriate for use to support the English language learning process in the fourth-grade elementary school independent curriculum.